2002
DOI: 10.1111/j.1749-6632.2002.tb04255.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin/Cortisol Ratio in Rheumatoid Arthritis

Abstract: Prolactin (PRL) and glucocorticoids are hormones involved in the regulation of the immune system. Rheumatoid arthritis (RA) is an inflammatory condition that presents a diurnal rhythm of disease activity. PRL/cortisol ratio, and IL-1beta and TNF-alpha levels were determined in patients with RA and in control subjects at 0600, 1000, 1400, 1800, 2200, and 0200 hours. In patients with RA we observed higher PRL/cortisol ratio at 0200 hours, whereas IL-1beta and TNF-alpha reached their highest serum levels at 0200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The size of abdominal aortic aneurisms has been correlated with the ratio of proinflammatory interleukin-6 to anti-inflammatory interleukin-10 [22]. Similarly, patients with rheumatoid arthritis had a ratio of proinflammatory prolactin to anti-inflammatory cortisol that corresponded with the diurnal onset of disease activity [23].…”
Section: Discussionmentioning
confidence: 99%
“…The size of abdominal aortic aneurisms has been correlated with the ratio of proinflammatory interleukin-6 to anti-inflammatory interleukin-10 [22]. Similarly, patients with rheumatoid arthritis had a ratio of proinflammatory prolactin to anti-inflammatory cortisol that corresponded with the diurnal onset of disease activity [23].…”
Section: Discussionmentioning
confidence: 99%
“…A peak of RA activity is clinically characterized early in the morning. Especially higher PRL/cortisol ratio during nocturnal hours together with increased levels of IL-1 and TNF-of the diurnal rhythm coincided with disease activity in patients with RA [102,103]. Decreased PRL response to hypoglycemic stress has been reported in RA patients, suggesting a close relationship between abnormal PRL secretion and HPA dysfunction [104,105].…”
Section: Prl In Immunopathogenesis Of Ramentioning
confidence: 96%
“…Although the HPA axis in RA appears normal, it has been suggested that there is an inherent defect in its failure to respond to inflammation with increased cortisol secretion (2,(11)(12)(13)(14). Straub and Cutolo (15) asked whether the chronic proinflammatory state depends on a persistent trigger (e.g.…”
Section: Known Effects Of Acute and Chronic Inflammation On The Hypotmentioning
confidence: 99%